Closure of sino-orbital fistula using glabellar rotation flap: A case report - Chakraborti, Chandana; Palchoudhury, Krittika; Das, Jayanta (Nepalese Journal of Ophthalmology, 2019)
Background: Sino-orbital fistulas (SOF) are a well-reported complication of orbitalexenteration and sinonasal carcinoma resection. Despite repair, however, complete fistula closure may be difficult.Case: A 79 –years-old man had undergone total exenteration of right orbit for spreading sqamous cell carcinoma of conjunctiva. Subsequently he developed two large sinoorbitalfistulae medially to the ethmoid sinus wall of the orbit. Post- operatively good socket hygiene was maintained but the fistulae increased in size. At 3 month follow-up, closure of the fistulae using glabellar rotation advancement flap was done. The defects have remained closed at follow-up with excellent cosmetic results. There is no recurrence of fistula or malignancy till date. Patient was cosmetically rehabilitated with spectacle prosthesis.Conclusion: Glabellar rotation flap for closure of medially situated sino- orbital fistulae is a good option with excellent cosmetic result.